2016
DOI: 10.1007/s11416-016-0273-3
|View full text |Cite
|
Sign up to set email alerts
|

Semantics-aware detection of targeted attacks: a survey

Abstract: In today's interconnected digital world, targeted attacks have become a serious threat to conventional computer systems and critical infrastructure alike. Many researchers contribute to the fight against network intrusions or malicious software by proposing novel detection systems or analysis methods. However, few of these solutions have a particular focus on Advanced Persistent Threats or similarly sophisticated multi-stage attacks. This turns finding domainappropriate methodologies or developing new approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 97 publications
(138 reference statements)
0
26
0
Order By: Relevance
“…Additionally, the adversary can also hack and acquire the credentials of a root user of the system. This can be carried out using various attack procedures available in the conventional attack catalog [30]. However, possessing the knowledge of a private database system or a remotely acquiring credentials of a root user would require exceptional capabilities for the adversary.…”
Section: Threat Modelmentioning
confidence: 99%
“…Additionally, the adversary can also hack and acquire the credentials of a root user of the system. This can be carried out using various attack procedures available in the conventional attack catalog [30]. However, possessing the knowledge of a private database system or a remotely acquiring credentials of a root user would require exceptional capabilities for the adversary.…”
Section: Threat Modelmentioning
confidence: 99%
“…For an in-depth look at related and similar work refer to Luh et al's literature survey [11] as well as the system's core publication [6].…”
Section: Related Workmentioning
confidence: 99%
“…12 Research has demonstrated the potential of using data mining techniques to identify hidden patterns in malware data to support SIEM analysis. Recent review papers detail the challenges facing by the SIEM analysis, particularly in the areas of intrusion 11 and attack detection.…”
Section: Related Workmentioning
confidence: 99%
“…Recent review papers detail the challenges facing by the SIEM analysis, particularly in the areas of intrusion 11 and attack detection. 12 Research has demonstrated the potential of using data mining techniques to identify hidden patterns in malware data to support SIEM analysis. 13 Another interesting approach is the use of latent semantic analysis to help reduce unnecessary noise in large datasets.…”
Section: Related Workmentioning
confidence: 99%